The Relationship Of Children's Knowledge About Covid 19 Prevention With Healthy Living Behavior In Class 3-6 State Elementary School: Hubungan Pengetahuan Anak Mengenai Pencegahan Covid 19 dengan Perilaku Hidup Sehat pada Anak Kelas 3-6 Sekolah Dasar Negeri - Astuti, Dyah Puji; Prabandari, Fitria; Mutoharoh, Siti; Sofiana, Juni (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The implementation of PHBS for students at school certainly requires the role of parents and teachers as companions in its implementation. Parents play a role in implementing PHBS activities at home, while the implementation of PHBS in schools is the responsibility of the teacher. Therefore, parents and teachers must understand the various health problems that may arise in children. This is related to the process of preventing and avoiding complications so as to create healthy, intelligent and accomplished Indonesian children. This study aims To find out the relationship between children's knowledge of COVID-19 prevention and healthy living behavior in grades 3-6 Methods: The method used by the researchers in this study was non-experimental with a correlational analysis research design through a cross sectional approach. Sampling for this study was taken by the entire population, namely 84 respondents. The research instrument used a questionnaire on the level of children's knowledge and healthy lifestyle behavior. Results: The level of knowledge of students in grades 3-6, Kebumen Regency is dominated by the level of knowledge in the good category with a frequency value of 56 respondents (66.5%). Healthy lifestyle behavior Students in grades 3-6 are dominated by healthy lifestyle behaviors in the good category with a frequency of 55 respondents (65.5%). There is a positive relationship between the level of knowledge of children with healthy lifestyle behavior of students in grades 3-6. This means that the better the child's level of knowledge regarding the prevention of COVID-19, the healthier lifestyle behavior of students in grades 3-6 will improve.Conclusion: There is a positive relationship between the level of knowledge of children with healthy lifestyle behavior of students in grades 3-6. Recommendation: It is hoped that students can continue to maintain and increase knowledge about preventing Covid-19 because it can improve habits for carrying out clean and healthy living behaviors for students.